The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/molecules25225308
|View full text |Cite
|
Sign up to set email alerts
|

Role of Bcl-2 Family Proteins in Photodynamic Therapy Mediated Cell Survival and Regulation

Abstract: Photodynamic therapy (PDT) is a treatment modality that involves three components: combination of a photosensitizer, light and molecular oxygen that leads to localized formation of reactive oxygen species (ROS). The ROS generated from this promising therapeutic modality can be lethal to the cell and leads to consequential destruction of tumor cells. However, sometimes the ROS trigger a stress response survival mechanism that helps the cells to cope with PDT-induced damage, resulting in resistance to the treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 96 publications
0
11
0
Order By: Relevance
“…Among the members of this family, there are pro-apoptotic proteins (e.g., Bid, Bax) and proteins that inhibit this process (e.g., Bcl-2). Thanks to these two opposite types of regulatory proteins, it is possible to maintain the homeostasis of the processes of this type of programmed cell death [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…Among the members of this family, there are pro-apoptotic proteins (e.g., Bid, Bax) and proteins that inhibit this process (e.g., Bcl-2). Thanks to these two opposite types of regulatory proteins, it is possible to maintain the homeostasis of the processes of this type of programmed cell death [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis is a highly regulated cell death mechanism. It involves the initiation of numerous pathways following the damages of several organelles [16]. Mitochondria play a key role in apoptosis regulation and any PS localized on the organelle triggered the process.…”
Section: Biochemical Effects Of Pdt and Reactive Oxygen Species (Ros)...mentioning
confidence: 99%
“…Mitochondria play a key role in apoptosis regulation and any PS localized on the organelle triggered the process. Leakage of the cytochrome c from the mitochondria into the cytosol can activate caspase proteins to induce signal transduction that leads to apoptosis [16,17]. Cell death by necrosis is extensive damage of cell components at PS site of action that results in leakage of intracellular material that can cause inflammation.…”
Section: Biochemical Effects Of Pdt and Reactive Oxygen Species (Ros)...mentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggested that ATO could promote the apoptosis-inducing effect of Met on HeLa cells. Bcl-2 family proteins are key molecules in the regulation of apoptosis, and can act directly or indirectly on mitochondria to perform their corresponding functions [30]. Compared with treatment of HeLa cells with Met or ATO alone, the combination of 40 mmol/L Met and 4 µmol/L ATO resulted in significant downregulation of the anti-apoptotic protein Bcl-2, significant upregulation of the pro-apoptotic protein Bax, and an increased Bax/Bcl-2 ratio (Figure 2B).…”
Section: Changes In Cell Morphologymentioning
confidence: 99%